The venomous secrets of the web droplets from the viscid spiral of the orb-weaver spider Nephila clavipes (Araneae, Tetragnatidae) - Salles, Heliana C.; Volsi, Evelyn Cristina F. R.; Marques, Mauricio R.; Souza, Bibiana M.; dos Santos, Lucilene D.; Tormena, Claudio F.; Mendes, Maria A.; Palma, Mario Sergio [UNESP] (Wiley-Blackwell, 2006)
The capture web of N. clavipes presents viscous droplets, which play important roles in web mechanics and prey capture. By using scanning and transmission electron microscopy, it was demonstrated that the web droplets are constituted of different chemical environments, provided by the existence both of an aqueous and a lipid layer, which, in turn, present a suspension of tenths of vesicles containing polypeptides and/or tipids. GC/EI-MS Analysis of the contents of these vesicles led to the identification of some saturated fatty acids, such as decanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, octadecanoic acid, and icosanoic acid, while other components were unsaturated fatty acids, such as (Z)-tetradec-9-enoic acid, (Z)-octadec-9-enoic acid, and (Z)-icosa-11-enoic acid; and polyunsaturated fatty acids like (9Z,12Z)-octadeca-9,12-dienoic acid, (9Z,12Z,15Z)-octadeca-9,12,15-trienoic acid, and (11Z,14Z)-icosa-11,14-dienoic acid. Toxic proteins such as calcium-activated proteinase and metalloproteinase jararhagin-like precursor were also identified by using a proteomic approach, indicating the possible involvement of these enzymes in the pre-digestion of spiders' preys web-captured. Apparently, the mixture of fatty acids are relatively toxic to insects by topical application (LD50 64.3 +/- 7.6 ng mg(-1) honeybee), while the proteins alone present no topical effect; however, when injected into the prey-insects, these proteins presented a moderate toxicity (LD50 40.3 +/- 4.8 ng mg(-1) honeybee); the mixture of fatty acids and proteins is very toxic to the preys captured by the web droplets of the viscid spiral of Nephila clavipes when topically applied on them (LD50 14.3 +/- 1.8ng mg(-1) honeybee).